Greenhouse gas emissions in Norway Do carbon taxes work? - Annegrete Bruvoll; Bodil Merethe Larsen (Statistics Norway, Research Department, 2002)
During the last decade, Norway has carried out an ambitious climate policy. The main policy tool is a relatively high carbon tax, which was implemented already in 1991. Data for the development in CO2 emissions since then provide a unique opportunity to evaluate carbon taxes as a policy tool. To reveal the driving forces behind the changes in the three most important climate gases, CO2, methane and N2O in the period 1990-1999, we decompose the actually observed emissions changes, and use an applied general equilibrium simulation to look into the specific effect of carbon taxes. Although total emissions have increased, we find a significant reduction in emissions per unit of GDP over the period due to reduced energy intensity, changes in the energy mix and reduced process emissions. Despite considerable taxes and price increases for some fuel-types, the carbon tax effect has been modest. While the partial effect from lower energy intensity and energy mix changes was a reduction in CO2 emissions of 14 percent, the carbon taxes contributed to only 2 percent reduction. This relatively small effect relates to extensive tax exemptions and relatively inelastic demand in the sectors in which the tax is actually implemented.
Keywords: H21; O13; Q40; 330; Greenhouse gas emissions; carbon taxes; applied general equilibrium model